Financial Integration and Portfolio Diversification: Evidence from CIVETS Stock Markets - Saleem, Kashif; Al-Hares, Osama; Ahmed, Sheraz (Scientific Research, 2016)
This paper investigates the extent of financial integration among a new group of six frontier markets called “CIVETS” by utilizing the multivariate GARCH framework of Engle and Kroner [1]. These countries are expected to show sustainable growth in productivity and domestic consumption over the next decade and are considered as potential corridor for the international investor from portfolio diversification point of view. We utilize weekly stock market return series of all the CIVIETS nations, and results exhibit significant return and volatility spillovers among all the markets under investigation. Our results reveal that there are significant linkages among CIVETS stock markets during the time of our analysis. However, the direction of relationship is asymmetric depending on the countries in the model. We believe, CIVIETS stock markets have full potential of being the future investment targets worldwide.
Keywords: GARCH-BEKK; Volatility Spillovers; Contagion; CIVETS Equity Markets; Portfolio Diversification